2019
DOI: 10.1111/echo.14474
|View full text |Cite
|
Sign up to set email alerts
|

“The Starry Sky.” A new intraprocedural three‐dimensional echocardiographic technique

Abstract: The NeoChord procedure is a micro‐invasive, trans‐ventricular, beating‐heart chordal replacement technique for patients with severe degenerative mitral valve regurgitation resulting from prolapsed or flail leaflets. Three dimensional transoesophageal echocardiographic guidance is crucial to assist the operator during the procedure. Equidistant placement of neochordae along the free edge of the prolapsing leaflet segment is important to ensure uniform stress distribution and to avoid damaging any of the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The use of three-dimensional (3D) TEE is already described as a fundamental tool to direct this beating-heart repair in terms of chordal implantation position and morphological analysis of the MV during and after neochordae traction and fixation. 5,6 Careful analysis of the morphological details of the LV chamber, in particular the anatomy of subvalvular apparatus and papillary muscle (PM) insertion, is important to plan the device navigation and choose the best access site. This is one of the most significant steps for procedural success and safety.…”
Section: Central Messagementioning
confidence: 99%
“…The use of three-dimensional (3D) TEE is already described as a fundamental tool to direct this beating-heart repair in terms of chordal implantation position and morphological analysis of the MV during and after neochordae traction and fixation. 5,6 Careful analysis of the morphological details of the LV chamber, in particular the anatomy of subvalvular apparatus and papillary muscle (PM) insertion, is important to plan the device navigation and choose the best access site. This is one of the most significant steps for procedural success and safety.…”
Section: Central Messagementioning
confidence: 99%
“…The efficacy and safety of this solution have already been demonstrated mainly thanks to the worldwide expansion of the Neochord experience. The market launch of this new device, as the development of many others under preclinical investigation, 7,[27][28][29][30][31][32] demonstrates, if there was still a need, the importance of a novel and alternative approach in mitral valve disease treatment. Artificial chordal implantation is an already validated technique in mitral valve surgery with proven results in acute and long-term outcomes, 33,34 usually associated with prosthetic ring annuloplasty.…”
mentioning
confidence: 99%
“…Trying to replicate surgery results, avoiding CPB and cardioplegic arrest, is ambitious, but it is worth the effort. Pursuing this aim, many studies have been published to optimize the Neochord procedure and the patients' selection, 7,[27][28][29][30][31][32] paving the road to better results for all the new devices entering the clinical arena. Therefore, the good short-term outcomes reported by Wang et al are not surprising and could potentially be confirmed at mid-and long-term follow-up.…”
mentioning
confidence: 99%